An eighteen-month follow-up of a pilot parent-delivered play-based intervention to improve the social play skills of children with attention deficit hyperactivity disorder and their playmates - Cantrill, A.; Wilkes-Gillan, S.; Bundy, A.; Cordier, Reinie; Wilson, N. (Wiley-Blackwell Publishing Asia, 2015)
Background: Children with attention deficit hyperactivity disorder (ADHD) experience significant ongoing social difficulties which occur in multiple contexts. Interventions designed to improve these social difficulties have demonstrated minimal effectiveness. Thus, there is a clear need to establish interventions that are effective in addressing the social difficulties of children with ADHD across contextsand in the long term. Aim: To examine the longterm effectiveness and appropriateness of a pilot parentdelivered intervention designed to improve the social play skills of children with ADHD and their playmates.Method: Participants included five children with ADHD who had completed the intervention 18-months prior, their typically developing playmates and mothers of children with ADHD. Blinded ratings from the Test of Playfulness were used to measure children’s social play: post-intervention and 18-months following the intervention in the home and clinic. Wilcoxon signed-ranks and Cohen’s-d calculations were used to measure effectiveness. Parents’ perspectives of the appropriateness of the intervention were explored through semi-structured interviews and data were analysed thematically.Results: The social play skills of children with ADHD and their playmates were maintained following the intervention in the home and clinic. Thematic analysis revealed four core-themes against an intervention appropriateness framework: new parenting tools, a social shift, adapting strategies over time and the next developmental challenge.Conclusion: The parent-delivered intervention demonstrated long-term effectiveness and appropriateness for improving children’s social play skills.Significance: These preliminary results are promising as maintaining treatment effects and achieving generalisation across contexts has remained an unachieved goal for most psycho-social interventions.